Review of: “Handbook HiBBer (Hijau, Bersih dan Berkelanjutan)”, first edition, by Tatang Parjaman et al., Universitas Galuh, 2022 - Mauladi, Mochamad Arief Rizki; Rachmah, Malinda Aptika (Interdisciplinary International Journal of Conservation and Culture, 2023)
The book was created by the university's conservation and culture team to serve as a guideline for the University of Galuh (UniGal) academic community in implementing a green campus. The book consists of 3 chapters: an introduction, an explanation of the work program, and strategic steps for the conservation and culture university.